Difference between revisions of "2007 iTest Problems/Problem 23"

(Undo revision 99013 by Skrublord420 (talk))
 
Line 32: Line 32:
  
 
== Solution ==
 
== Solution ==
Let <math>Y = I = N = G = 3^{1/4}.</math>
 
 
Let <math>a = x^2 - 3x</math>.  Substituting that in results in
 
Let <math>a = x^2 - 3x</math>.  Substituting that in results in
 
<cmath>a^2 + 5a + 6</cmath>
 
<cmath>a^2 + 5a + 6</cmath>
Line 38: Line 37:
 
<cmath>(a+2)(a+3)</cmath>
 
<cmath>(a+2)(a+3)</cmath>
 
<cmath>(x^2-3x+2)(x^2-3x+3)</cmath>
 
<cmath>(x^2-3x+2)(x^2-3x+3)</cmath>
The first part is factorable into <math>(x-2)(x-1)</math>.  The second part isn’t — and the discriminant is <math>3^2 - 4 \cdot 3 = -3</math>.  With the imaginary factors found, by [[Vieta's Formulas]], the product of the non-real roots is <math>3 = YING = \boxed{\textbf{(V) } Ying}</math>.
+
The first part is factorable into <math>(x-2)(x-1)</math>.  The second part isn’t — and the discriminant is <math>3^2 - 4 \cdot 3 = -3</math>.  With the imaginary factors found, by [[Vieta's Formulas]], the product of the non-real roots is <math>\boxed{\textbf{(F) }3}</math>.
  
 
==See Also==
 
==See Also==

Latest revision as of 16:48, 24 November 2018

Problem

Find the product of the non-real roots of the equation \[(x^2-3x)^2+5(x^2-3x)+6=0\]

$\text{(A) } 0\quad \text{(B) } 1\quad \text{(C) } -1\quad \text{(D) } 2\quad \text{(E) } -2\quad \text{(F) } 3\quad \text{(G) } -3\quad \text{(H) } 4\quad \text{(I) } -4\quad$

$\text{(J) } 5\quad \text{(K) } -5\quad \text{(L) } 6\quad \text{(M) } -6\quad \text{(N) } 3+2i\quad \text{(O) } 3-2i\quad$

$\text{(P) } \frac{-3+i\sqrt{3}}{2}\quad \text{(Q) } 8\quad  \text{(R) } -8\qquad \text{(S) } 12\quad \text{(T) } -12\quad \text{(U) } 42\quad$

$\text{(V) Ying} \quad \text{(W) } 207$

Solution

Let $a = x^2 - 3x$. Substituting that in results in \[a^2 + 5a + 6\] Factoring that (and substituting back) leads to \[(a+2)(a+3)\] \[(x^2-3x+2)(x^2-3x+3)\] The first part is factorable into $(x-2)(x-1)$. The second part isn’t — and the discriminant is $3^2 - 4 \cdot 3 = -3$. With the imaginary factors found, by Vieta's Formulas, the product of the non-real roots is $\boxed{\textbf{(F) }3}$.

See Also

2007 iTest (Problems)
Preceded by:
Problem 22
Followed by:
Problem 24
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 TB1 TB2 TB3 TB4
Invalid username
Login to AoPS